Meningkatkan Minat Beli Konsumen Di Tiktok Shop : Peran E-Trust dan E-Service Quality Pada Produk Fashion Dalam Era Pemasaran Digital - M Haris; Andi Azhar (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of e-trust and e-service quality on consumer purchase intention for fashion products in TikTok Shop. A quantitative approach was used with a survey method to collect data from respondents selected by purposive sampling. The research instrument was a questionnaire compiled based on research variable indicators and measured using a Likert scale. The collected data were analyzed using statistical tests, including descriptive analysis and linear regression to test the relationship between variables. The results showed that e-trust and e-service quality have a positive and significant effect on consumer purchase intention. Specifically, e-trust related to consumer trust in the platform and sellers in TikTok Shop has a greater impact than e-service quality which focuses on the quality of digital services provided. These findings emphasize the importance of the role of e-trust and e-service quality in shaping purchasing decisions in the era of digital marketing. E-commerce sellers and platforms need to pay more attention to increasing transparency, transaction security, and the quality of the shopping experience to encourage the growth of consumer purchase intention and loyalty.